Pembentukan Karakter Melalui Nilai-Nilai Edukatif Puasa Ramadhan Menurut Prespektif Al-Ghazali - Fatakhul Huda (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2022)
Abstrak Character building through the educational values ​​of Ramadan fasting according to Al-Ghazali's perspective, namely fasting is preventing and leaving and there is no secret of action that appears in it. And fasting is an inner exercise with only patience. Al Ghazali said that fasting itself is secret, no action is seen in it, while all acts of obedience are witnessed and seen by many people. Fasting no one sees but Allah SWT. Al-Ghazali's view of fasting is that fasting is divided into two, namely the first is outward fasting which includes: minimal levels, namely fasting only in the month of Ramadan. The highest level is the fasting of the Prophet David as, the middle level is fasting a third of the year. Second, spiritually, in terms of secrets, fasting is divided into three, namely: general fasting, special fasting and special special fasting. Second, the formation of character through the educational values ​​of Ramadan fasting according to Al-Ghazali's perspective, namely: Fasting is a tool to control lust from thirst, hunger and intercourse, from sunrise to sunset. In the sense that the work of lust must be controlled by reason, because it is very influential in the framework of forming human morals, and it is hoped that morals will grow in people who are fasting, namely fasting educates humans with patient traits, so that they can control themselves from everything that breaks fasting and the value of reward fasting solely to worship Allah SWT and be grateful for the favors obtained from Him so that it has implications for character building, namely increasing faith. and piety, forming trust, justification, honesty, it is hoped that the character of social care and individual discipline will grow and maintain physical health.